2018
DOI: 10.1155/2018/8539674
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis and Security Enhancement of Three Authentication Schemes in Wireless Sensor Networks

Abstract: Nowadays wireless sensor networks (WSNs) have drawn great attention from both industrial world and academic community. To facilitate real-time data access for external users from the sensor nodes directly, password-based authentication has become the prevalent authentication mechanism in the past decades. In this work, we investigate three foremost protocols in the area of password-based user authentication scheme for WSNs. Firstly, we analyze an efficient and anonymous protocol and demonstrate that though thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Amin et al [47] presented a user authentication protocol for distributed cloud computing environment composed of IoT devices. However, Challa et al [48] and Li et al [49] demonstrated several security pitfalls in the scheme [47], such as privileged-insider and impersonation attacks. Apart from these, Amin et al's scheme [47] fails to guarantee some important requirements like user anonymity and forward secrecy properties.…”
Section: Literature Surveymentioning
confidence: 99%
“…Amin et al [47] presented a user authentication protocol for distributed cloud computing environment composed of IoT devices. However, Challa et al [48] and Li et al [49] demonstrated several security pitfalls in the scheme [47], such as privileged-insider and impersonation attacks. Apart from these, Amin et al's scheme [47] fails to guarantee some important requirements like user anonymity and forward secrecy properties.…”
Section: Literature Surveymentioning
confidence: 99%
“…Privileged insider attack is a security threat that has been ignored for a long time, and even protocol designers are not aware of the serious consequences of such attack [52], which has been mentioned in [52,53]. When scrutinizing scheme [42], we find that neither Jung et al's scheme can resist the security risk of privileged insider attack, nor can Shin and Kwon's scheme, which is an improved version of Jung et al's scheme, defend against privileged insider attack.…”
Section: ) Privileged Insider Attackmentioning
confidence: 99%
“…The operations mainly include exclusive-or, symmetric keys and hash functions and thus the communication overhead is low even for the resourceconstrained IoTs devices. However, Li, Wenting, et al [16] pointed out that the method cannot specifically solve the problem about user anonymity and forward secrecy since some private information is preserved by the smart card. In addition, Aman, Muhammad Naveed, et al [17] and Guin, Ujjwal, et al [18] proposed mutual authentication schemes with physically unclonable function (PUF) in the environment of IoTs.…”
Section: A Internet Of Things (Iots) Architecturementioning
confidence: 99%